The logic of what is appropriate in terms of environmental sanitation in human settlements in Costa Rica - Chamizo García, Horacio Alejandro (2011)
Develops a content´s analysis of the formal normative framework of the environmental sanitation in human settlements in Costa Rica. The theoretical point of departure is the new institutionalisms and the theory of networks of public policy that oriented the selection of laws and regulations in four settings of management that should function articulated. The analysis of content showed that the dismemberment of the play’s rule and the concentration of the power in the technicians, does not favor the problem’s approach in its complexity, the network management and the construction of an active citizenship that permit to put in practice the principle statement of the social production of the health.